Design of optical fiber delay line with large delay range and low insertion loss - Wang, Kai; Liu, Anqi; Kong, Xinxin; Wu, Zhou; Zhang, Rui; Zhang, Wenxi (Frontiers in Physics, 2024)
For the application of continuously adjustable optical fiber delay lines, a large delay range can increase the instrument's measurement range. Increased insertion loss of components will reduce the signal-to-noise ratio of the collected signal, ultimately limiting the measurement accuracy of the instrument. In order to take into account both large delay range and low insertion loss in design, a spatial light transmission and fiber coupling model based on scalar diffraction theory was established and the insertion loss was equivalently calculated through the coupling efficiency of the coupling lens. Then, we analyze the impact of optical fiber delay line’s structural parameters and adjustment errors on coupling efficiency. By optimizing lens group parameters and limiting adjustment tolerances, we can reduce the insertion loss of optical fiber delay lines in a large delay range and conduct experimental verification. Considering various influencing factors, we use a lens group with a focal length of 12mm, achieving a coupling efficiency of no less than 92.7% within the delay range of 0-1m. This theoretical model provides a new quantitative analysis method for improving the performance of the optical fiber delay line.